Heimatkunde in der DDR. Didaktische Ansätze und Spannungsfelder : Eine fallorientierte Analyse ausgewählter Stundenkonzeptionen - Fischer, Christian 1980- (Von der DDR-Heimatkunde zum Sachunterricht. Die Grundschule vor und nach 1989, 2021)
Local history lessons in the GDR were intended to make a significant contribution to the political and natural history education of children in the first four years of school. But what didactic approaches and what areas of tension were present in local history lessons? This question forms the starting point for the study of three selected lesson concepts from local history lessons in the GDR. The study follows the approach of historical subject teaching research. An important point is also the question of what conclusions can be drawn from the analysis of the historical lesson concepts for current didactic and pedagogical thinking. Translated with DeepL.com (free version)